Hermeneutic Review of the Meanings of Angling Darma Relief at Candi Jago - I Nyoman Suardina; Marina Wardaya (Randwick International of Social Science Journal, 2023)
The purpose of this research is to discover the cultural relationship between the Angling Darma reliefs at Candi Jago. Candi Jago is the only place where you can find Angling Darma relief. The Angling Darma relief on Jago Temple is a testament to the glory of the civilization of the Hindu-Buddhist dynasty in Indonesia. However, not many Indonesians know the meaning of the Angling Darma relief at Candi Jago. No one has yet discussed the cultural aspect in relation to the angling darma relief motif on Jago temple in a hermeneutic review. The problems are: 1) What is the shape of the relief of Angling Darma at Candi Jago?.; 2) Is there a correlation between the Angling Darma reliefs at Candi Jago and culture? 3) What is the relationship between Angling Darma reliefs and culture from a hermeneutic perspective? This study uses a qualitative method with a hermeneutic paradigm. All primary data was successfully collected based on observations of the reliefs at Candi Jago. All secondary data were searched through a literature study of Candi Jago. The totality of the data was analyzed qualitatively in a hermeneutical review. The findings revealed: 1) an Angling Darma relief in the form of a painting of a character named Angling Darma; 2) a correlation between culture and Angling Darma reliefs at Candi Jago; and 3) a moral meaning emphasizing firm belief and chivalrous attitude in cultural relations and the Angling Darma reliefs at Candi Jago.